2010
DOI: 10.1590/s0365-05962010000200020
|View full text |Cite
|
Sign up to set email alerts
|

Caso para diagnóstico

Abstract: A doença de Dowling-Degos é uma genodermatose rara, caracterizada principalmente por hiperpigmentação reticular progressiva de áreas flexurais. Apesar de apresentar evolução benigna, pode estar associada a neoplasias da pele. Além disso, as alterações cutâneas características potencialmente ocasionam prejuízo psicossocial, devido aos danos estéticos significativos. Os autores descrevem um caso dessa doença associado a ceratoacantoma e sintetizam os conceitos atuais sobre ela.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…It is very often associated with epidermoid cysts, keratoacanthoma, squamous cells carcinoma, abscess, suppurative hidrosadenitis, seborrheic keratosis and pilonidalis cysts. 2 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is very often associated with epidermoid cysts, keratoacanthoma, squamous cells carcinoma, abscess, suppurative hidrosadenitis, seborrheic keratosis and pilonidalis cysts. 2 …”
Section: Introductionmentioning
confidence: 99%
“…3 , 4 , 5 This resembles the appearance of a solar lentigo, but with epidermal atrophy, melanin incontinence and perivascular lymphocytic infiltrate. 2 Accordingly to the similarity in clinical and histological features, many authors consider RAK and DDD different phenotypes of a single disorder. 2 In literature the authors found only few cases of overlap RAK-DDD (about a dozen), including family cases described until four generations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation